Portland Water Fluoridation: A Newspaper Analysis. Issue 2 (21st July 2016) - Bianchi, Allison; Bergren, Martha Dewey; Lewis, Patricia Ryan
Abstract: Portland, Oregon is the largest city in the United States without community water fluoridation (CWF). A newspaper analysis was conducted of the failed 2013 CWF campaign to evaluate anti‐fluoridation and pro‐fluoridation messaging provided by newspapers during the campaign. News content was categorized by type and slant (pro‐fluoridation, anti‐fluoridation, or neutral) and 34 variables were tabulated (23 anti‐fluoridation, 11 pro‐fluoridation). Results showed overall messaging was slightly pro‐fluoridation, as compared to anti‐fluoridation or neutral content (35%, 32%, and 33% respectively). Editorial content was 85% pro‐fluoridation and 15% anti‐fluoridation. The most frequent anti‐fluoridation variables were alternatives to water fluoridation, mass/forced medication and concerns about the political process. Conversely, tooth decay and social justice were the most commonly cited pro‐fluoridation variables. Newspapers can be influential in shaping public policy opinions in the fight for community water fluoridation.